Determinant Factors of Corporate Social Responsibility Disclosures in Hospitality and Tourism Companies in Indonesia and Thailand - Saarce Elsye Hatane; Jennifer Eugene Chandra; I Gusti Ayu Purnamawati; Hatane Semuel (Indonesian Journal of Sustainability Accounting and Management, 2023)
Corporate Social Responsibility (CSR) is increasingly recognized as one aspect of sustainable business development. Within the tourism industry, CSR plays an important aspect in integrating social and environmental concerns in strategies, policies, and business operations in interactions with the community and the company’s stakeholders. This study aims to assess and examine the critical factors that influence the formation of Corporate Social Responsibility Disclosure (CSRD) in hospitality and tourism sector companies. The motivation for this research stems from previous studies that showed contradictory results regarding the factors that influence CSRD. Furthermore, research on the factors that influence CSRD in Indonesia and Thailand’s hospitality and tourism industries is rarely done. This study uses company data from 2015 to 2019 with the Generalized Least Square and Weighted Least Square methods in data analysis. This study examines the effect of Profitability, Leverage, Firm Value, Liquidity, and Firm Size on CSRD. In addition, this study contributes to research on the influence of Firm Value on CSRD, which is still rarely done. This study shows that Leverage and Firm Size have a significant positive effect on CSRD, while Firm Value has a significant negative impact on CSRD.